2021
DOI: 10.21608/anj.2021.69935.1025
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Blood Transfusion Outcomes in Preterm Infants admitted to Neonatal Intensive Care Unit (NICU): A Retrospective Analytical Study

Abstract: Background: Red blood cell (RBC) transfusions in preterm infants have been associated with increased risk of short-term morbidities, as necrotizing enterocolitis (NEC), bronchopulmonary dysplasia (BPD), retinopathy of prematurity (ROP) and intracranial hemorrhage (ICH). Aim of work: To study the relationship between RBC transfusions and short-term morbidities in preterm infants. Patients and Methods: Retrospectively, the relationship between RBC transfusions, number of transfusions and short-term morbidities w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…In the present study, regarding need of oxygen: 31.7 of cases needed MV, 27.3 needed CPAP, 27.4 needed nasal prongs, while 13.7 didn't need oxygen support. Which supports our findings; Gomaa and Abdelkhalik (17) found a moderately positive link between the quantity of transfusions and the length of mechanical ventilation as well as a moderately negative correlation between the quantity of transfusions and the length of CPAP. A strong negative correlation existed between the amount of transfusions received in the first month, birth weight, and gestational age.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, regarding need of oxygen: 31.7 of cases needed MV, 27.3 needed CPAP, 27.4 needed nasal prongs, while 13.7 didn't need oxygen support. Which supports our findings; Gomaa and Abdelkhalik (17) found a moderately positive link between the quantity of transfusions and the length of mechanical ventilation as well as a moderately negative correlation between the quantity of transfusions and the length of CPAP. A strong negative correlation existed between the amount of transfusions received in the first month, birth weight, and gestational age.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, Liao et al (12) , found that time of hospital stay in observation group was (41±16.9) days, and in control group was (18±7.4) days. RBC transfusion in the first week was essentially related to death in preterm neonates as shown in the study of Gomaa and Abdelkhalik (17) and Wang et al 20) . Vamvakas and Blajchman (21) suggested that transfusion may be associated with multi-organ system failure, pro-inflammatory mechanisms, and transfusionrelated immunomodulation.…”
Section: Discussionmentioning
confidence: 86%